Performance Evaluation of Greek Domestic and International Equity Mutual Funds - Charkiolakis, Georgios (2016)
The present study investigates the performance of Greek domestic and international equity mutual funds using a daily data sample of 44 funds in total, 23 domestic and 21 international, for the period from 1/1/2011 to 26/6/2015. The methods applied for performance measure are the Jensen’s alpha coefficient, based on the Capital Asset Pricing Model (CAPM), ranking the funds according to Sharpe and Treynor ratio, the quadratic Treynor-Mazuy model, the Cubic model and the Merton & Henriksson model. The second empirical part includes the long term volatility estimation for each of the 44 mutual fund using the Garch (1, 1) model. The overall results suggest that the Greek equity mutual funds have not been able to provide out-performance. Alphas for equity mutual funds, both domestic and international are insignificantly different from zero. In addition, there is no evidence of timing and forecasting abilities by the fund managers whatsoever. Finally, it seems that Garch (1, 1) long term volatility can be a good indicator about the future volatility. The results of our analysis support those of the current literature.